Considerations in Selecting Turkey Bedding Materials - Jesse Grimes; Mahmoud Sharara; Praveen Kolar (German Journal of Veterinary Research)
Abstract The commercial turkey of today is a descendant of wild, then domesticated, turkeys from North America originating in regions of old Mexico. The modern commercial turkey enjoys a wide range of acceptance in many countries. Turkey production evolved rapidly from 1950 forward with many changes in production and management. Turkey production changed from range rearing to mostly total confinement. Rearing birds under increased density in confinement facilities has created both opportunities and challenges. Once confined, organic materials have been used as bedding (also referred to as litter). There have been many materials evaluated and used for bedding. Availability, cost, and bird performance were early key considerations. More recently, bird health and welfare are now important considerations as well. Optimal management programs of the modern turkey reared in confinement can be elusive and difficult to define. However, controlling litter moisture which aids in reducing ammonia and footpad dermatitis should be a key management component of confinement rearing. Therefore, bedding choice and litter management in turkey production require thoughtful consideration and active management.